THE ENZYMATIC EFFECT (α-AMYLASE) ON VISCOSITY AND CARBOHYDRATE COMPOSITION OF MAIZE FLOUR MODIFIED - Suarni Suarni; Tj. Harlim; Ambo Upe; Abd R. Patong (Universitas Gadjah Mada, 2007)
Technology is required in making new product of maize flour. Enzymatic modification of three varieties of maize flours i.e. MS2, Srikandi and Local product has been conducted using α-amylase from mung bean sprouts has been carried out in Laboratorium Bioproses BB Pascapanen Bogor. A research was performed used the flour without addition of sprouts (as control) and with addition of 10, 20, 30 % of sprouts. Parameters observed were the change in viscosity of the maize flour; amylose, glucose and oligosaccharide contents. Results showed that there were changes in polymerization degree, dextrose equivalent, amylase content, viscosity (50 oC), viscosity (50 ºC/20΄), and carbohydrate composition. An enzymatic treatment using 20% of sprout to the three varieties gave results as follows: amylose content was 20.02 - 24.02%, viscosity (50 ºC) was 210 - 230 BU, and viscosity (50 ºC/20΄) was 200 - 220 BU. Functional properties of the flour fulfilled with the soft texture product, such as food material for children under five years old. Data of the modified flour can be utilized by consuments as an alternative food material.